Analysis of Magnesium as A Prognostic Marker for Chronic Kidney Disease at Dr. Wahidin Sudirohusodo Hospital - Bahri, Suryanti; Kartini, Ani; Widaningsih, Yuyun (Indonesian Association of Clinical Pathologist and Medical laboratory, 2025)
Magnesium (Mg) is an essential mineral that plays a role in many organ functions, including the kidneys. Magnesium has roles in regulating mitochondrial function, inflammatory processes, immune defenses, heart excitability, and blood pressure. Chronic Kidney Disease (CKD) can disrupt Mg balance and can have an impact on the progression and prognosis of CKD. This study aimed to analyze Mg levels as a prognostic marker for CKD. This was a descriptive retrospective study with a cross-sectional approach. The total sample consisted of 136 subjects with CKD patients, comprising stage I (n=3), stage II (n=2), stage III (n=11), stage IV (n=26), and stage V (n=94) based on the KDIGO classification. According to KDIGO, they were categorized as low risk (n=5), moderate risk (n=11), and high risk (n=120). Magnesium levels were assessed using the colorimetric method. Statistical analysis was performed using SPSS version 25, including the Kolmogorov-Smirnov test, a Kruskal-Wallis test, the least significant difference, and Spearman's correlation test. The cut-off point was determined using the ROC curve. Results were considered statistically significant if p< 0.05. This study demonstrated a significant positive correlation between eGFR values and Mg levels falling into the moderate category (0.2250<R<0.500). Characteristics of research subjects showed that the lowest Mg levels (1.81) were found in high risk prognosis (p<0.001) and stage 5 CKD (1.72) (p<0.001). The optimal cut-off point for Mg levels in CKD patients was 2.40 mg/dL, with a sensitivity of 76% and specificity of 69%. Magnesium levels can be used as a prognostic marker for CKD.